The Boy on the Rooftop: Universal Apostolic Preference Three and Four of the Society of Jesus (Hekima Review, 2020)
Young people have shared intersecting vulnerabilities based on their age and their susceptibility to the deteriorating long-term health of Planet Earth, our common home. Added to these might be specific, socially constructed, sometimes systemic, disadvantages of poverty, race, gender, sexuality or geography. (This is glaringly evident in the Covid-19 pandemic.) These intersections invite a broad apostolic response. The third and fourth Apostolic Preferences of the Society of Jesus (for 2019to 2029) encourage Jesuits and our companions in mission to journey with young people and to care for our common home, respectively. The present contribution argues that one necessitates the other. As Laudato Si’ is seminal in its holistic response to environmental and social issues, so our Christian response to young people and care for creation does not permit compartmentalisation. For example, young people’s ecoanxiety is best combated by a proactive engagement in significant environmentally beneficial actions.